Vocabulary learning using student-created class vocabulary lists - G. Clint Denison; Imogen Custance (Vocabulary Learning and Instruction, 2020)
In this article, we describe the pedagogical basis for class vocabulary lists (CVLs) and their implementation using Google Sheets. CVLs allow students to collaborate and build “notebooks” of vocabulary that they feel is important to learn. CVL choices of students (N= 53) in three classes of mixed non-English majors and one informatics class were compared against frequency-based lists (British National Corpus/Corpus of Contemporary American English Word Family Lists [BNC/COCA], New General Service List [NGSL], Test of English for International Communication [TOEIC] Service List [TSL]) using the Compleat Web Vocabulary Profiler (Web VP) to determine the usefulness of the selected vocabulary. An information technology keywords list, constructed using AntConc and AntCorGen, was compared against the informatics group’s CVL to determine if those students were choosing field-appropriate vocabulary. Results suggest that when given autonomy to choose vocabulary, students generally select useful and relevant words for their contexts (e.g, simulation, virtual, privacy, artificial, denuclearization, aftershock, heatstroke) and that CVLs supplement frequency-based lists in beneficial ways.